Statistical Properties of the Capacity of Double Nakagami-m Channels for Applications in V2V Dualhop Communication Systems - Rafiq, Gulzaib; Hogstad, Bjørn Olav; Pätzoldt, Matthias (IntechOpen, 2011)
None